Interreligious Dialogue and Convergent Hermeneutics: A Challenge to Address by Christian Theology - Simon, Benjamin (The ecumenical review, 2021)
The link between religions and several issues of contemporary relevance lead to the need for interreligious dialogue today. However, interreligious dialogue is not about creating a unifying hermeneutic leading to convergence, as many approaches in our day tend to be. For religions to be in fruitful conversation, there is no need for levelling differences and denying one’s own convictions. Core theological convictions need not be up for discussion in dialogue. Rather, a hermeneutic of difference may be used that allows differences to stand in a respectful space. An interreligious conviviality that allows dialogue participants to learn from each other, share with each other, and celebrate with each other can lay perspectives for an interreligious future.